2021
DOI: 10.1016/j.ajic.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Examining instruments used to measure knowledge of catheter-associated urinary tract infection prevention in health care workers: A systematic review

Abstract: Examining instruments used to measure knowledge of catheter-associated urinary tract infection prevention in healthcare workers: a systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The findings reported in this review also support the need for solid theoretical foundations to define the constructs of knowledge and attitude from which such instruments need to be developed. Previous researchers of similar studies have reported a variation of constructs used for measurement instruments addressing inappropriate antibiotic use [ 61 ]. Varying definitions of knowledge and attitudes exist [ 17 , 29 ] and some researchers fail to define the constructs measured [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported in this review also support the need for solid theoretical foundations to define the constructs of knowledge and attitude from which such instruments need to be developed. Previous researchers of similar studies have reported a variation of constructs used for measurement instruments addressing inappropriate antibiotic use [ 61 ]. Varying definitions of knowledge and attitudes exist [ 17 , 29 ] and some researchers fail to define the constructs measured [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported in this review also support the need for solid theoretical foundations to define the constructs of knowledge and attitude from which such instruments need to be developed. Previous researchers of similar studies have reported a variation of constructs used for measurement instruments addressing inappropriate antibiotic use [61]. Varying definitions of knowledge and attitudes exist [17,29] and some researchers fail to define the constructs measured [62].…”
Section: Plos Onementioning
confidence: 99%